Safety Analysis of Boom-Supported Membrane Deployment - MORI, Osamu; SUGIHARA, Ahmed Kiyoshi; KUSUMOTO, Tetsuya (TRANSACTIONS OF THE JAPAN SOCIETY FOR AERONAUTICAL AND SPACE SCIENCES AEROSPACE TECHNOLOGY JAPAN, 2025)
A lightweight membrane has the potential to be a useful platform for a variety of on-orbit uses. Boom-supported multifunctional membranes have recently attracted attention because they can be attached to a satellite body and have solar arrays or antennas mounted on their surface. Although reliable deployment is crucial for their successful operation, the potential for interference between the boom and the membrane presents a significant risk. Thus, this paper provides a framework for performing a safety analysis of the membrane deployment. We define a potentially dangerous region where interference from membranes and booms may occur and evaluate the level of deployment safety by employing a multi-particle approach to simulate membrane deployment. This study focuses on the boom-supported membrane component of the HELIOS (Harvesting Energy with Lightweight Integrated Origami Structure) mission, and investigate strategies to mitigate the risks related to membrane and boom interference. The results show that for safe and reliable membrane deployment, the deployment speed and bending forces of the membrane must be considered.